A systematic review of the effect of The Daily Mile™ on children’s physical activity, physical health, mental health, wellbeing, academic performance and cognitive function - Gavin Breslin; Medbh Hillyard; Noel Brick; Stephen Shannon; Brenda McKay-Redmond; Barbara McConnell (PLoS ONE, 2023)
Background A minority of children in the United Kingdom meet the recommended physical activity guidelines. One initiative which has been introduced to try and increase the physical activity levels of school children is The Daily Mile™ (TDM). The aim of this review was to determine the effect of TDM on children’s physical activity levels, physical health, mental health, wellbeing, academic performance and cognitive function. Methods Six databases were systematically searched from TDM’s inception (2012) to 30th June 2022. Studies were included if they involved school-aged children (aged 4–12 years), taking part in TDM and measured at least one pre-defined outcome. Results Thirteen studies were included from the 123 studies retrieved. Longer-term participation in TDM was found to increase moderate-to-vigorous physical activity and physical fitness. None of the studies reported a significant change in Body Mass Index or academic performance. An acute bout of TDM was not found to improve cognitive function, however one good-quality study reported that longer-term participation in TDM increased visual spatial working memory. There was evidence from one fair-quality design study that TDM can improve mental health in the short term. There were no significant effects on wellbeing, however scores on self-perceptions improved mainly for children with low baseline self-perceptions. Conclusion There is evidence to show that TDM can increase physical activity and physical fitness. However, higher-quality research, with adequate participant randomisation and longer-term, post-intervention follow-up is needed to ensure that any changes accurately reflect the components of TDM and are sustained beyond an intervention time frame. Policy recommendations of TDM increasing PA levels in the short term are supported by the evidence in this review. However, long-term improvement on mental health, wellbeing, academic performance and cognitive function requires further good-to excellent quality research. Promisingly, several protocol articles that include randomised controlled trials with long term follow-up have been published. These higher-quality design studies may provide a stronger evidence-base on the effects of TDM on children’s health and should underpin future recommendations in public health policy. Systematic review registration PROSPERO CRD42022340303.